Functional Characterization of PknI-Rv2159c Interaction in Redox Homeostasis of Mycobacterium tuberculosis - Venkatesan, Arunkumar; Palaniyandi, Kannan; Sharma, Divakar; Bisht, Deepa; Narayanan, Sujatha (Frontiers in Microbiology, 2016)
Mycobacterium tuberculosis adapts to stress conditions by responding to the signals from its external environment. M. tuberculosis genome encodes 11 eukaryotic like serine/threonine protein kinases (STPK) and their importance in regulating the physiology and virulence of the bacteria are being explored. Previous study from our lab identified the M. tuberculosis STPK, PknI interacts with two peroxidase proteins such as Rv2159c and Rv0148. In this study, we have characterized the biological function behind the PknI-Rv2159c interaction in M. tuberculosis. Point mutation of Ala-Gly-Trp motif identified that only Ala49 and Gly50 amino acids of Rv2159c are responsible for interaction and there is no phosphorylation involved in the PknI-Rv2159c interaction. Rv2159c is a member from the carboxymuconolactone decarboxylase family with peroxidase activity. Enzymatic assays with catalytic site point mutants showed that Cys84 of Rv2159c was responsible for its alkylhydroperoxidase activity. Interestingly, interaction with PknI increased its peroxidase activity by several folds. Gene knockdown of Rv2159c in M. tuberculosis showed increased sensitivity to peroxides such as cumene hydroperoxide and hydrogen peroxide. Proteomic analysis of differentially expressing Rv2159c strains by 2D gel electrophoresis and mass spectrometry revealed the differential abundance of 21 proteins. The total absence of oxidoreductase, GuaB1 suggests the essential role of Rv2159c in redox maintenance. Our findings provide new insights on signaling mechanisms of PknI in maintaining the redox homeostasis during oxidative stresses.